Staphylococcus epidermidis’ Overload During Suckling Impacts the Immune Development in Rats - Morales-Ferré, Carla; Franch, Àngels; Castell, Margarida; Olivares, Mónica; Rodríguez-Lagunas, María J.; Pérez-Cano, Francisco J. (Frontiers in Nutrition, 2022)
Mastitis is an inflammation of the mammary gland occurring in 3 - 33% of the breastfeeding mothers. The majority of mastitis cases have an infectious etiology. More than 75% of infectious mastitis are caused by Staphylococcus epidermidis and Staphylococcus aureus and involves breast milk microbiota dysbiosis, which, may have an impact in lactating infant. The aim of this study was to analyze in rats during the suckling period and later in life the impact of a high and a low overload of Staphylococcus epidermidis, similarly as it occurs during the clinical and the subclinical mastitis, respectively. From day 2 to day 21 of life, suckling rats were daily supplemented with low (Ls group) or high (Hs group) dose of S. epidermidis. Body weight and fecal humidity were periodically recorded. On day 21 and 42 of life, morphometry, hematological variables, intestinal gene expression, immunoglobulin (Ig) and cytokine profile and spleen cells’ phenotype were measured. Although no differences were found in body weight, Ls and Hs groups showed higher body length and lower fecal humidity. Both doses induced small changes in lymphocytes subpopulations, reduced the plasma levels of Ig and delayed the Th1/Th2 balance causing a bias towards the Th2 response. No changes were found in cytokine concentration. The low dose affected the Tc cells intestinal homing pattern whereas the high dose had an impact on the hematological variables causing leukocytosis and lymphocytosis and also influenced the intestinal barrier maturation. In conclusion, both interventions with Staphylococcus epidermidis overload during suckling, affects the immune system development in short and long term.